A new species and four new records of Amanita (Amanitaceae; Basidiomycota) from Northern Thailand - Benjarong Thongbai (2018)
© 2016 Magnolia Press. Mushrooms belonging to the genus Amanita were collected during a fungal biodiversity study in northern Thailand in 2012-2014. Morphological characteristics and molecular phylogenetic analyses were used to identify the mushrooms to species. Amanita castanea is described as new to science and compared with phenetically and phylogenetically similar species. It is assignable to Amanita stirps Citrina within Amanita series Mappae. Four other species, A. concentrica, A. rimosa, A. cf. rubromarginata and A. zangii are first reports for Thailand; detailed morphological and molecular data are provided for the Thai material.